(untitled) (Revista Apotheke, 2019)
Being and Being steeped in creative states has been for years a founding choice. I invented words, images and artistic propositions at the same time. In this article I cut part of this production and I make links between Poem IX of the book of poems Caracol é uma casa que se anda. The central theme in both is CASA in a rather broad sense. Dialogue with writers, philosophers, artists and art educators. In them I anchor my anxieties and the ways of activating minimals of the world so that they see potent forms of art in lit lives.